Images of women in eighteenth century English chapbooks, from banal bickering to fragile females - Fromm, Katherine Barber (2000)
Eighteenth-century English chapbooks, an under-examined historical source, provide a rich panoply of images presented for popular consumption in cheap, ephemeral books. As part of popular culture, this humble literature changed over the course of the century. Of interest here are the images presented to women during this most significant century of chapbooks. Those of earlier decades retold traditional fairy tales and legends and reprinted jest books. In addition, there is a recurring strand of bickering and humorous exchanges between men and women. Ballads that depicted conjugal and marital relationships often found their way into chapbooks, and other chapbooks borrowed from and embellished upon the ballad tradition. Laments of domineering women, advice about consuming creatures, and lists of aggravated complaints present fresh and direct commentaries across the centuries upon the vagaries of everyday life;By about 1750, however, the contents in many chapbooks duplicated the emerging novel's themes of fragile and dependent females. By 1790 there are two other discernible trends produced by the cultural wars of that decade. 'Fulminations and polemics' written by disgruntled men railed against the behavior of women. There was a fine line between the tilt toward misogynistic complaints or pent-up tensions and frustrations. The other trend, resulting from the promises of reform and emancipation celebrated heroic women who displayed unusual valor in battle;The final chapters compare the activities of a female Robinson Crusoe, a resourceful woman with the hero of Daniel Defoe's 1719 epic. The saga of Mary Jane Meadows provides us with another perspective on gender. It also promotes another perspective on the novel, since many post-1750 chapbooks followed the style and content and borrowed their techniques. Like novels of this century, introspection and an emphasis on the individual clearly mark Meadows' account of personal struggle. A comparison of the elements of religion, government, the state of nature, and technology reveal the impact of gender. Clues within the text led to the conclusion first that the story was written by Charlotte Smith, a literary figure of some reputation. Although only circumstantial evidence leads to that conclusion, the evidence is compelling;These many chapters are offered as cultural studies of eighteenth century popular culture. Certainly trends in this humble literature deserve analysis, but a strand of linear progress cannot be contemplated. The shift from fresh and open exchanges to flat displays of female dependence suggests that the vitality of the Oral Tradition was another element of the 'world we have lost' when print became the dominant mode of expression